Diagnosis of Metaplastic Breast Carcinoma: Keratin OSCAR Versus Other Cytokeratins. Issue 9 (October 2016) - Galera, Pallavi; Khan, Ashraf; Kandil, Dina
Abstract : Metaplastic breast carcinoma (MBC) is a heterogenous group of tumors that diverge from conventional glandular differentiation. The metaplastic component can be focal or may be present purely posing diagnostic challenges. Since MBC may show focal immunostaining or may even be negative for some cytokeratins (CK), different CKs are often needed to prove their epithelial origin. OSCAR is a relatively new broad-spectrum anti-CK antibody. Thirty MBC cases diagnosed at our institution were retrieved, including 7 spindle cell carcinomas. Representative slides were immunostained for CK-OSCAR, CK-AE1/AE3, CAM5.2, CK-903, and CK5/6. Nineteen spindle cell lesions were used as controls, including 6 malignant and 10 borderline phyllodes tumor, 1 inflammatory pseudotumor, 1 solitary fibrous tumor, and 1 nodular fasciitis case. All 30 cases (100%) of metaplastic carcinomas were positive for CK-OSCAR, compared with 27/30 (90%, P =0.076) for CK-AE1/AE3, 21/30 (70%, P ⩽0.01) for CK-903, 19/30 (63.3%, P ⩽0.01) for CAM5.2, and 15/30 (50%, P ⩽0.01) for CK5/6. All control cases were negative for CK-OSCAR. All 7 spindle cell carcinomas were also positive for CK-OSCAR (100%) compared with 6/7 (85.7%) for CK-AE1/AE3, 4/7 (57%) for CK-903, 3/7 (42.8%) for CAM5.2, and 2/7 (28.5%) for CK5/6. Our data show that CK-OSCAR is more sensitive than other individual CKs in diagnosing MBC. Coupled with high specificity, CK-OSCAR may potentially be used in lieu of a panel of CKs to identify the epithelial origin of these tumors, especially in spindle cell tumors. This is particularly useful in limited core biopsy specimens, to help guide treatment and simultaneously lower testing costs.